Perception and intention to use e-learning from students' point of view- an evidence from Malaysia local university / Salina Mad ... [et al.] - Mad, Salina; Omar, Nor Alwani; Sarudin, Ezzah Suraya; Aziz, Nurul Hidayah (Universiti Teknologi MARA, Perlis, 2020)
Education landscape has changed dramatically due to Covid19 pandemic as in many country, conventional or face-to-face teaching and learning is no longer an option to avoid the spread of a virus. E-learning become one of the best alternative to ensure education process could continue because experts believe world could only recover from this crisis in another two years. This paper will delve into students’ perspective about e learning and their willingness to use e-learning. Technology Acceptance Model (TAM) was used to outlined this study. Majority of the student have an idea about what is e-learning. They also agree that e-learning able to be accomplished learning and assessment proses as well as enable the interaction among students and student with instructor. Result also indicate, majority of the students have positive opinion towards e-learning nevertheless they prefer e-learning to be embedded in their education process (hybrid learning) as they are still prefer to have some level of face to face learning. However, this result cannot be used to generalize the opinion of all university’s’ student as diploma student tend to feel more comfortable to have face-to-face interaction with lecturer because they are in the transition period from school to university.